INTEGRATING HYPERTONIA REHABILITATION, INTRAORAL REHABILITATION, AND ANXIETY MANAGEMENT FOR COMPREHENSIVE PATIENT CARE- PART1 - Lucian Stefan Burlea; Doriana Agop Forna; Mihaela Salceanu; Violina Budu; Vlad Proca; Bogdan Petru Bulancea; Tudor Hamburda; Maria Antonela Beldiman (Romanian Journal of Oral Rehabilitation, 2024)
As stomatognatic system dysfunctions, hypertonias are quite common. As premedication, miorelaxants, adjuvants for inflammatory processes (which result in antalgic hypertonic phenomena), and during local anesthesia through neuromuscular transmission blockage, miorelaxants are a class of pharmacological agents with various structures and mechanisms of action that are highly helpful in treating stomatognatic dysfunctions. The most current medication utilized for stomatognatic system miorelaxation is Botox, which has a favorable local administration impact in a variety of clinical circumstances and during stomatological operations. It also provides comfort during mandibulo-cranial repositioning and centric relation maneuvers.